What was the Alamo? - Pollack, Pam; Belviso, Meg; Groff, David 1956- (New York, New York, USA Grosset & Dunlap, an Imprint of Penguin Group (USA) Inc, 2013)
""Remember the Alamo!" is still a rallying cry more than 175 years after the siege in Texas, where a small band of men held off about two thousand soldiers of the Mexican Army for twelve days. The Alamo was a crucial turning point in the Texas Revolution, and led to the creation of the Republic of Texas. With 80 black-and-white illustrations throughout and a sixteen-page black-and-white photo insert, young readers will relive this famous moment in Texas history"--
"Two hundred Americans held off more than two thousand soldiers of the Mexican Army for twelve days before defeat. Only two Texans survived. The siege was a crucial turning point in the Texas Revolution, and led to the creation of the Republic of Texas. How many kids even knew there was a Republic of Texas? Now they will! With 80 black-and-white illustrations throughout and a sixteen-page black-and-white photo insert, young readers will relive the battle at the Alamo!"--
The world around us
Includes bibliographical references
1
Keywords: JUVENILE NONFICTION / Adventure & Adventurers; JUVENILE NONFICTION / History / Mexico; JUVENILE NONFICTION / History / Military & Wars; JUVENILE NONFICTION / History / United States / 19th Century; JUVENILE NONFICTION / History / United States / General; Alamo (San Antonio, Tex.) -- Juvenile literature; Alamo (San Antonio, Tex.) -- Siege, 1836 -- Juvenile literature; San Antonio (Tex.) -- Buildings, structures, etc -- Juvenile literature; Texas -- History -- To 1846 -- Juvenile literature